2005
DOI: 10.1111/j.1464-5491.2005.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized‐LDL levels are changed during short‐term serum glucose variations and lowered with statin treatment in early Type 2 diabetes: a study of endothelial function and microalbuminuria

Abstract: In early obese Type 2 diabetic patients, serum ox-LDL levels are influenced by short-term serum glucose variations and lowered with cerivastatin therapy. During cerivastatin treatment, improved flow-mediated endothelium-dependent dilation was associated with decrements in circulating ox-LDL levels and the hyperinsulinaemia-induced urinary albumin excretion was blunted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Previous studies have investigated the relationship between oxLDL and FMD in specific patient populations (11)(12)(13), but this relation has not yet been evaluated in a large-population-based sample. We have used FMD data from the Hoorn Study, a community-based cohort study among elderly men and women, to assess the suitability of the oxLDL/LDL-c and oxLDL/apoB100 ratios to correct for LDL particle number.…”
mentioning
confidence: 99%
“…Previous studies have investigated the relationship between oxLDL and FMD in specific patient populations (11)(12)(13), but this relation has not yet been evaluated in a large-population-based sample. We have used FMD data from the Hoorn Study, a community-based cohort study among elderly men and women, to assess the suitability of the oxLDL/LDL-c and oxLDL/apoB100 ratios to correct for LDL particle number.…”
mentioning
confidence: 99%
“…Although it is widely accepted that oxidative stress serves to impair endothelial function, only a limited numbers of studies have demonstrated the correlation between the plasma markers of oxidative stress, such as TBARS and oxLDL, and the extent of FMD in clinical studies. 31,32 In the preliminary study, we did not find correlations between plasma TBARS or 8-iso PGF2α levels and the plasma BH4/BH2 ratio or FMD (%) (data not shown). Although the source of plasma pteridine has not been clarified yet, it is assumed that plasma levels of pteridine reflect endothelial pteridine metabolism because the endothelium is directly in contact with blood and is the major site for formation of peroxynitrite that oxidizes BH4.…”
Section: Discussionmentioning
confidence: 71%
“…Evidence also suggests that dyslipidaemia may promote retinal microvascular inflammation and the formation of pericyte ghosts in diabetes, independently of hyperglycaemia [27,28]. Modification of LDL by glycation and oxidation represents a qualitative dyslipidaemia that is accentuated in both type 1 and type 2 diabetes [9][10][11]. Although a role of modified LDL in the development of macrovascular disease (atherosclerosis) is well documented, its involvement in diabetic retinopathy is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…LDL modified by oxidation and glycation, is elevated in diabetic plasma [9][10][11] and is established as playing an important role in atherogenesis in both diabetic and non-diabetic patients [12]. However, its role in diabetic retinopathy is less clear.…”
Section: Introductionmentioning
confidence: 99%